IMPLEMENTATION OF ISLAMIC EDUCATION IN BUILDING RELIGIOUS VALUES IN STUDENTS AT SMP MUHAMMADIYAH 3 SUKABUMI - Hilman, Cecep; Rohmah, Siti; Muti, Irma; Sutarman, Sutarman (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Religious education plays a strategic role in shaping students' character based on religious values in the midst of globalization challenges. Purpose: This study aims to examine the implementation of Islamic Education in instilling religious values in students at SMP Muhammadiyah 3 Sukabumi. Methods: This study used a qualitative descriptive approach, with data obtained through purposive and snowball sampling methods. Data collection techniques include observation, interviews, and documentation, while data analysis is carried out descriptively. Results: Findings show that the implementation of religious values is well executed through daily activities and special programs such as Qur'an Learning Centers, joint prayer, and religious talent development. The assessment is carried out systematically through attitude evaluation, behavioral monitoring, and religious practices in accordance with the 2013 Curriculum. Conclusion: This study concludes that a systematic approach to religious education in SMP Muhammadiyah 3 Sukabumi is effective in instilling religious values.